Capital Structure and Investment Growth Opportunity of Listed Pharmaceutical Firms in Nigeria (Asian Business Research, 2017)
This study assesses the impact of capital structure on investment opportunity growth, using listed pharmaceutical firms in Nigeria. The main objective of the study is to ascertain the level to which capital structures influences the investment opportunity growth of listed pharmaceutical firms in Nigeria. The methodology employed is the use of secondary data and the ex-post facto research design. The population of the study is all 7 pharmaceutical firms listed on the Nigerian Stock Exchange as at 31st December, 2013. The study used regression as a tool of analysis. Findings show that Short term debt, total debt and performance were found to have significant, negative and strong effect on investment growth opportunity of Listed Pharmaceutical firms in Nigeria, while long term debt have no effect on investment growth opportunity of Listed Pharmaceutical firms in Nigeria, within the sturdy period. The study recommends that pharmaceutical firms should maintain a minimal level of short term debt because tying down too much of it current assets will reduce investment opportunity, also the management of listed Pharmaceutical firm should increase the level at which the organization uses long term debt to finance its business activities, as this may go a long way in increasing the investment opportunity potentials of the organizations, we also recommend that mmanagement should reduce the combination of its short term debt and long term debt and channel such to a highly profitable investment so that so that it will encourage them to invest more in other business opportunity that will bring more fortune to the business and shareholders at largemore room.